Zygophylax brownei Billard 1924 - Gu, Zhangjie; Ruthensteiner, Bernhard; Moura, Carlos J.; Liu, Lihua; Zhang, Rui; Song, Xikun (Zenodo, 2022)
ZYGOPHYLAX BROWNEI BILLARD, 1924 (FIG. 8) Zygophylax brownei : Ramil & Vervoort, 1992: 65–70, figs 13a–d, 14a–c (synonymy). Type locality: Bay of Biscay, north-east Atlantic; 186 m. Specimens examined: Three colonies from the Gulf of Cadiz, one of them fertile; see details in Supporting Information, Table S1. Molecular sequences: 16S rRNA, 18S rRNA, 28S rRNA and COI genes (this study); see sequence details in Supporting Information, Table S3. Published as part of Gu, Zhangjie, Ruthensteiner, Bernhard, Moura, Carlos J., Liu, Lihua, Zhang, Rui & Song, Xikun, 2022, Systematic affinities of Zygophylacidae (Cnidaria: Hydrozoa: Macrocolonia) with descriptions of 15 deep-sea species, pp. 52-87 in Zoological Journal of the Linnean Society (Zool. J. Linn. Soc.) (Zool. J. Linn. Soc.) 196 on page 66, DOI:10.1093/zoolinnean/zlac036, http://zenodo.org/record/7035312